Optical Frequency Down-Conversion With Bandwidth Compression Based on Counter-Propagating Phase Matching - Guo, Dong-Jie; Yang, Ran; Liu, Yi-Chen; Duan, Jia-Chen; Xie, Zhenda; Gong, Yan-Xiao; Zhu, Shi-Ning (Frontiers in Physics, 2021)
Optical quantum network plays an important role in large scale quantum communication. However, different components for photon generation, transmission, storage and manipulation in network usually cannot interact directly due to the wavelength and bandwidth differences, and thus interfaces are needed to overcome such problems. We propose an optical interface for frequency down-conversion and bandwidth compression based on the counter-propagating quasi-phase-matching difference frequency generation process in the periodically-poled lithium niobate on insulator waveguide. We prove that a separable spectral transfer function can be obtained only by choosing proper pump bandwidth, thus relaxing the limitation of material, dispersion, and working wavelength as a result of the counter-propagation phase-matching configuration. With numerical simulations, we show that our design results in a nearly separable transfer function with the Schmidt number very close to 1. With proper pump bandwidth, an photon at central wavelength of 550 nm with a bandwidth ranging from 50 GHz to 5 THz can be converted to a photon at central wavelength of 1545 nm with a much narrower bandwidth of 16.5 GHz.